Regulation and competition policy in the european union-functions of the regulators - Güven, Işıl (My University, 2007)
Bu çalısmanın amacı, Avrupa Birligi içerisinde serbestlesme süreci yasayan dogal tekellerin regülasyon (düzenleme) kurallarının ve bu süreçte büyük bir sorumluluk altında olna düzenleyici kurumların incelenmesidir. Çalısmanın birinci bölümünde, kavram olarak regülasyon çerçevelendirilecek. Bunu ek olarak, regülasyonun amacı, iyi regülasyon ilkeleri ve regülasyon türleri üzerinde durulacaktır. Ayrıca bu bölümde, regülasyon rekabet hukuku ile iliskilendirilecektir. kinci bölümde, düzenleyici kurumlar, amaçları, fonksiyonları ele alınacak; düzenleyici modellerden söz edilecektir. Bunun yanında, düzenleyici kurumlar ile rekabeti düzenleyici kurumlar arasındaki ilski üzerinde durulacaktır. Son olarak, Avrupa Birligi içerisinde dogal tekellere iliskin faaliyet gösteren düzenleyici kurumlar incelecektir. Üçüncü bölümde dogal tekellerin tanımı yapılacak; bu baglamda Avrupa Birligi Hukuku çerçevesinde kamu hizmeti irdelecektir. Regülasyon ve özellestirme iliskisi ile dogal tekellerin serbestlesmesi ele alınacaktır. Dördüncü bölümde, Avrupa Birligi kapsamında serbestlesme süreci incelecek; daha sonra dogal tekel özelligi gösteren sektörlerden enerji sektörü üzerinde durulacaktır. Bu baglamda, söz konusu sektörde faaliyet gösteren düzenleyici kurumlar hukuki çerçeve dahilinde ele alınacaktır. Besinci bölümde, Türkiye’de serbestlesme ve özellestirme sürecine göz atılacak; bu baglamda Türkiye’deki düzenleyici kurumlar hukuki çerçeve dahilinde incelenecektir. Son olarak yukarıda sözü edilen konular baglamında tespitler yapılacaktır.

The purpose of this study is basically to emphasize the EU regulatory policy regarding natural monopolies in the liberalization process and regulatory agencies which are having a post of great responsibility. In the first section of this study, the main features of regulation as a concept will be outlined. Thereby the aim of regulation, principles of good regulation, and types of regulation will be examined. In addition to regulatory regime will be associated with competition law. In the second section of this study, regulators (defined as regulatory agencies), their objectives and functions will be mentioned thoroughly; regulatory models clarified. On the other hand relationship between regulatory agencies and competition authorities will be analyzed. The European Union perspective regarding regulatory agencies in the network industries will be outlined. In the third section, the definition of natural monopoly will be indicated. In this context, the concept of public service in the context of European Union law will be analyzed. In this section also relationship between regulation and privatization and liberalization of natural monopolies will be outlined. In the fourth section, general survey on liberalization process in The European Union will be analyzed briefly. Hereafter, the structure and regulation of energy sectorelectricity and gas industries will be examined particularly in detail. In this respect, functions of regulators in the mentioned sector will be outlined in the context of legal framework. In the fifth section, liberalization and privatization process in Turkey will be analyzed. Regulatory agencies in Turkey will be also examined. Following that, in the last part of the study, it will end with concluding remarks in the context of analyzed points above-mentioned.
Keywords: Avrupa Birliği Hukuku; Regülasyon; Serbestleşeme